2016
DOI: 10.1152/ajpheart.00334.2016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aging and coronary artery disease on sympathetic neural recruitment strategies during end-inspiratory and end-expiratory apnea

Abstract: In response to acute physiological stress, the sympathetic nervous system modifies neural outflow through increased firing frequency of lower-threshold axons, recruitment of latent subpopulations of higher-threshold axons, and/or acute modifications of synaptic delays. Aging and coronary artery disease (CAD) often modify efferent muscle sympathetic nerve activity (MSNA). Therefore, we investigated whether CAD (n = 14; 61 ± 10 yr) and/or healthy aging without CAD (OH; n = 14; 59 ± 9 yr) modified these recruitme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
40
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 40 publications
10
40
1
Order By: Relevance
“…Thus, both approaches converge on the conclusion that low threshold axons observable under baseline conditions are recruited more frequently in at least some disease states. This pattern is different that than observed with ischemic heart disease with clinically normal ejection fraction where increases in baseline MSNA burst frequency occur but with little change in the number of APs per burst (Badrov et al 2016a). Therefore, the modified recruitment threshold of axons available under baseline conditions may be related to cardiac function and, by inference, cardiac sensory input to central autonomic control (Millar et al 2015).…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Thus, both approaches converge on the conclusion that low threshold axons observable under baseline conditions are recruited more frequently in at least some disease states. This pattern is different that than observed with ischemic heart disease with clinically normal ejection fraction where increases in baseline MSNA burst frequency occur but with little change in the number of APs per burst (Badrov et al 2016a). Therefore, the modified recruitment threshold of axons available under baseline conditions may be related to cardiac function and, by inference, cardiac sensory input to central autonomic control (Millar et al 2015).…”
Section: Discussioncontrasting
confidence: 73%
“…In addition to, or perhaps because of, changes in baseline control outlined in the above paragraph, age and cardiovascular disorders may affect reflexive AP recruitment. Specifically, in contrast to similarly aged adults, patients with ischemic heart disease (but normal ejection fraction) expressed a near-absent ability to recruit larger APs during apneas of similar length (Badrov et al 2016a). Similarly, heart failure patients with reduced ejection fraction expressed diminished ability to increase the APs/burst despite the large stress imposed by a preventricular contraction (Maslov et al 2012), yet recruitment of new APs was normal.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…() breathed with nitrogen until SnormalpO2 decreased to ∼90%, then they held their breath for ∼5 s. Based on our experience, ∼10% reduction in SnormalpO2 rarely activates peripheral chemoreceptors and triggers a robust HVR in young, healthy subjects. Furthermore, voluntary end‐expiratory apnoea is known to be accompanied by various changes (hypoxia, hypercapnia, cessation of lung inflation and increased central drive to breath) that lead to marked sympathoexcitation, vasoconstriction, increase in blood pressure and slight increase in HR (Badrov, Lalande, Olver, Suskin, & Shoemaker, ; Patel, Heffernan, Ross, & Muller, ), and these effects are accentuated in hypoxic conditions (Leuenberger, Hardy, Herr, Gray, & Sinoway, ). In conclusion, it seems questionable whether the results by Eckberg et al.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this group has previously shown that older adults have a reduced ability to recruit previously silent AP subpopulations during sympathoexcitation (Badrov et al . 2016). The analysis of baroreflex gain within AP subpopulations may help to further elucidate mechanisms involved in exaggerated sympathoexcitation or declines in sympathetic baroreflex sensitivity with ageing.…”
mentioning
confidence: 99%